The relationship between the concept of Akinnah Al-Qalb with human capital development - Jamaludin, Abdul Kamil; Mat Akhir, Noor Shakirah (Future Academy, 2019)
The development of human capital is a plan which requires a priority as a foundation for a sustainable, virtuous and glorious civilization. Until today copious efforts for self-development have revolved around the physical, mental and emotional aspects. Education of the heart is apparently lacking in the human capital development process. The concept of Akinnah al-Qalb refers to the barrier that exists in developing the human heart. Hence, the exploration into this concept is essential to the development of virtuous human capital. Previous research has focused on the factors that contribute to human capital development; nonetheless, no attempt has been made to explore the aspects which hinder human capital development, with specific reference to the Quran. Hence, this paper aims to explore the Quranic verses that are correlated to the notion of Akinnah al-Qalb, their characteristics and the description of its features based on the opinions of various religious scholars. Qualitative method was virtuously engaged in this study by referring to the analyses made on Quranic verses by mufassirun that are linked to Akinnah al-Qalb concept. The findings of the present study have been able to explain the concept of Akinnah al-Qalb and describe its connection with the human heart and consequently its significance in human capital growth.